Supporting in grief and burnout of the nursing team from pediatric units in Chilean hospitals - Paula Vega Vega; Rina González Rodriguez; Natalie Santibáñez Galdamez; Camila Ferrada Molina; Javiera Spicto Orellana; Antonia Sateler Villanueva; Jose Bustos Melo (SciELO, 2018)
ABSTRACT Objective To know the levels of Burnout Syndrome and perception of grief support in nursing teams of oncology and pediatric intensive care in public hospitals in Chile. Method A study of descriptive cross-sectional design. The Maslach Burnout Inventory and the Grief Support Health Care Scale were applied to university-level and technical nursing professionals between March and November 2015. An analysis to compare the means was performed with use of the Student's t-test, and the level of significance was set at 5%. Results The study included 153 professionals. Results show 4% of professionals have Burnout Syndrome (BS) and 89% are at risk of having it. Oncology professionals are at higher risk as they present higher levels of emotional exhaustion and lower levels of personal fulfillment. Half of professionals have a high level of perception of grief support, which is greater in the oncology team. Conclusion Professionals working in pediatric oncology units are at increased risk of Burnout Syndrome and grief support may be a mediating factor in this process.